Improving China's Generation Z Hospitality Competencies through Counseling in Bali - Wisnawa, I Made Bayu (Jurnal Pengabdian Masyarakat Bestari, 2024)
This community service activity aims to enhance the hospitality competencies of Generation Z from China through counseling conducted in Bali. The counseling, attended by 25 participants aged 19 to 22, employed interactive lectures, group discussions, and practical simulations to improve skills in Front Office and Housekeeping operations. The methods included pretests and posttests to evaluate participant understanding. Results demonstrated a significant increase in knowledge, with an average score improvement from 52 (pretest) to 80 (posttest). These findings suggest that the program successfully enhanced the participants' competencies, preparing them for careers in the international hospitality industry.